Can Private Equity Funds Act as Strategic Buyers? Evidence from Buy-and-Build Strategies - Dyaran Bansraj; Han Smit; Vadym Volosovych (Tinbergen Institute, 2020)
By holding assets longer and increasingly focusing on growth strategies private equity firms enter the territory of strategic buyers. In one such strategy, a private equity firm buys a company and then builds on that “platform” through add-on acquisitions. We ask whether such serial (buy-and-build) acquisition strategies deliver operating synergies, as expected from strategic buyers, or rather are a form of “window-dressing.” We collect a sample of buy-and-build strategies from seven major European markets and find that the profitability of these strategies improves more than that of the comparable strategies, constructed by us from stand-alone companies. We analyze a number of operating outcomes across various strategy sub-types and confirm that these operational improvements are consistent with the synergy interpretation.
Keywords: L2; G24; G34; 330; Private Equity; Leveraged Buyouts; Buy-and-Build; Operating Performance; Synergies